2008
DOI: 10.1007/s10709-008-9327-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing genetic diversity in Gossypium arboreum L. cultivars using genomic and EST-derived microsatellites

Abstract: The cultivated diploid, Gossypium arboreum L., (A genome) is an invaluable genetic resource for improving modern tetraploid cotton (G. hirsutum L. and G. barbadense L.) cultivars. The objective of this research is to select a set of informative and robust microsatellites for studying genetic relationships among accessions of geographically diverse G. arboreum cultivars. From more than 1,500 previously developed simple sequence repeat (SSR) markers, 115 genomic (BNL) and EST-derived (MUCS and MUSS) markers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 28 publications
2
41
2
1
Order By: Relevance
“…Another reason is that the high portion of trinucleotide repeats in coding regions may be due to the exertion of selection pressure for selecting particular single amino acid stretches (Morgante et al 2002). Also the most informative SSRs contained C10 repeats which are in agreement with the previous studies (Vigouroux et al 2002;Qureshi et al 2004;Kantartzi et al 2009). It was also observed that position of the SSR loci on the chromosome has no effect on the corresponding PIC values (Lacape et al 2003(Lacape et al , 2007.…”
Section: Genetic Characterizationsupporting
confidence: 85%
See 1 more Smart Citation
“…Another reason is that the high portion of trinucleotide repeats in coding regions may be due to the exertion of selection pressure for selecting particular single amino acid stretches (Morgante et al 2002). Also the most informative SSRs contained C10 repeats which are in agreement with the previous studies (Vigouroux et al 2002;Qureshi et al 2004;Kantartzi et al 2009). It was also observed that position of the SSR loci on the chromosome has no effect on the corresponding PIC values (Lacape et al 2003(Lacape et al , 2007.…”
Section: Genetic Characterizationsupporting
confidence: 85%
“…In this study, we proposed 22 (11 BNLs and 11 MGHES) out of the 75 SSRs-based on their high PIC values (PIC C 5.0) and potential to amplify distinct DNA fragments for calculating the extent of genetic diversity among the 36 Gossypium species. Such findings were reported in multiple investigations including 39 SSRs for cotton genetics studies (Lacape et al 2007) and 25 SSRs for G. arboreum accessions (Kantartzi et al 2009). Large number of informative gSSRs had di-nucleotide repeats while larger portion of informative EST-SSRs had tri-nucleotide motif.…”
Section: Genetic Characterizationsupporting
confidence: 68%
“…The PIC values ranged from 0.021 to 0.80 (average 0.206) ( Table 2). The average PIC obtained during the present study was less to that obtained by Kantartzi et al (2009) (average PIC 0.42), while analyzing genetic diversity in G. arboreum cultivars using microsatellites, though the range obtained by them was also different (0.00 to 0.68). Liu et al (2006) also reported high average PIC (0.31), compared to that obtained in present study, and the average PIC value obtained by Lacape et al (2007) was also higher (average 0.55) than our value.…”
Section: Microsatellite Diversitycontrasting
confidence: 83%
“…Efforts have also been made for genetic diversity analysis of selected G. arboreum germplasm using different markers like RAPD (Rana and Bhat 2004;Mahmood et al 2009;Mandaliya et al 2010;Deosarkar et al 2010;Dongre et al 2011), ISSR Khandagale et al 2007;Bardak and Bolek 2012) and microsatellites or simple sequence repeats (SSRs) Liu et al 2006;Dongre et al 2007;Kantartzi et al 2009;Deosarkar et al 2010;Dongre et al 2011;Noormohammadi et al 2013), though no study explored the polymorphism among the six races of G. arboreum. So, the present work was designed to study genetic diversity among elite genotypes of six different races of G. arboreum using microsatellite markers, since microsatellites markers have edge over other marker system in cultivar fingerprinting and diversity studies,…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular markers such as AFLP (Rana et al, 2005;Westengen et al, 2005), RAPD (Vafai-Tabar et al, 2004), SSR (Lacape et al, 2007;Kantartzi et al, 2009;Luo et al, 2010) and ISSR (Dongre et al, 2004) have been used in upland cotton germplasm analysis, which is helpful to reveal the genetic diversity of these varieties in future breeding. Molecular markers such as SSR Chen et al, 2005;Li et al, 2009;Wu et al, 2010), ISSR (Jiang et al, 2008) and SRAP (Li et al, 2008) have also been applied in determining the genetic diversity of sea-island cotton.…”
Section: Introductionmentioning
confidence: 99%